Scotland: Currency Options and Public Debt. (February 2014) - Armstrong, Angus; Ebell, Monique
This paper considers which currency option would be best for an independent Scotland. We examine three currency options: being part of a sterling currency zone, adopting the euro, or having an independent currency. No currency option is the best when considered against all criteria. Therefore, making the decision requires deciding which criteria are most important. Recent events around the world, particularly in Europe, show that it is essential to consider how an independent Scotland would seek to adjust to adverse economic circumstances. In economists' terms, it is important to think through the 'off-equilibrium' adjustment paths of each of the currency options. The amount of public debt, and so the capacity for a fiscal response, is a critical determinant of these paths and therefore of the optimal currency choice. Since commitment to a currency union by an independent country can only be conditional, an independent Scotland might find it optimal to abandon the currency union in the future if the financial stability advantages to having its own currency begin to outweigh any disadvantages due to trade and transactions costs.